Genetic and biochemical analysis of severe hypertriglyceridemia complicated with acute pancreatitis or with low post-heparin lipoprotein lipase mass - Takashi Suzuki; Makoto Kurano; Akari Isono; Takuya Uchino; Yohei Sayama; Honami Tomomitsu; Daiki Mayumi; Ruriko Shibayama; Toru Sekiguchi; Naoki Edo; Kiyoko Uno-Eder; Kenji Uno; et al. (Endocrine Journal)
Severe hypertriglyceridemia is a pathological condition caused by genetic factors alone or in combination with environmental factors, sometimes leading to acute pancreatitis (AP). In this study, exome sequencing and biochemical analyses were performed in 4 patients with hypertriglyceridemia complicated by obesity or diabetes with a history of AP or decreased post-heparin LPL mass. In a patient with a history of AP, SNP rs199953320 resulting in LMF1 nonsense mutation and APOE rs7412 causing apolipoprotein E2 were both found in heterozygous form. Three patients were homozygous for APOA5 rs2075291, and one was heterozygous. ELISA and Western blot analysis of the serum revealed the existence of apolipoprotein A-V in the lipoprotein-free fraction regardless of the presence or absence of rs2075291; furthermore, the molecular weight of apolipoprotein A-V was different depending on the class of lipoprotein or lipoprotein-free fraction. Lipidomics analysis showed increased serum levels of sphingomyelin and many classes of glycerophospholipid; however, when individual patients were compared, the degree of increase in each class of phospholipid among cases did not coincide with the increases seen in total cholesterol and triglycerides. Moreover, phosphatidylcholine, lysophosphatidylinositol, and sphingomyelin levels tended to be higher in patients who experienced AP than those who did not, suggesting that these phospholipids may contribute to the onset of AP. In summary, this study revealed a new disease-causing gene mutation in LMF1, confirmed an association between overlapping of multiple gene mutations and severe hypertriglyceridemia, and suggested that some classes of phospholipid may be involved in the pathogenesis of AP.